2018
DOI: 10.1029/2018ja025925
|View full text |Cite
|
Sign up to set email alerts
|

Electron Cyclotron Harmonic Wave Instability by Loss Cone Distribution

Abstract: We propose a new method to construct a controllable and quantifiable loss cone distribution. Then, we derive a linear growth rate formula of the electrostatic mode for a realistic and arbitrary distribution function. Such formula is used to perform a parametric study of instability analysis of the electron cyclotron harmonic (ECH) wave in a plasma consisting of electron loss cone distribution and isotropic cold electron distribution. We find (1) the peak linear growth rate and the corresponding wave frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…And, indeed, Figure e demonstrates that ECH wave intensity peaks at δB ‖ minima (i.e., during intervals of decreasing E l ). Although the peak ECH wave growth rate from this free energy source should be at small harmonic numbers (Liu et al, ; Ashour‐Abdalla & Kennel, ; Ni et al, ), THEMIS‐D observed peak ECH wave amplitudes at the fourth through seventh harmonics. Moreover, the role of loss cone anisotropy in the periodic ECH wave excitation is unclear.…”
Section: Spacecraft Data and Methodsmentioning
confidence: 99%
“…And, indeed, Figure e demonstrates that ECH wave intensity peaks at δB ‖ minima (i.e., during intervals of decreasing E l ). Although the peak ECH wave growth rate from this free energy source should be at small harmonic numbers (Liu et al, ; Ashour‐Abdalla & Kennel, ; Ni et al, ), THEMIS‐D observed peak ECH wave amplitudes at the fourth through seventh harmonics. Moreover, the role of loss cone anisotropy in the periodic ECH wave excitation is unclear.…”
Section: Spacecraft Data and Methodsmentioning
confidence: 99%
“…For the sake of completeness, we list the electrostatic electron cyclotron harmonic waves for minor resonant interactions with radiation belt electrons and a contribution to diffuse aurora at L > 8 (Liu et al, ; Meredith et al, ; Meredith, Horne, Thorne, & Anderson, ; Shaw & Gurnett, ; Zhang et al, ).…”
Section: Particle Loss In the Inner And Outer Zonesmentioning
confidence: 99%
“…PLEASE CITE THIS ARTICLE AS DOI: 10.1063/5.0002336 perpendicular direction. 33 We calculated f (v||, v⊥) at the position where nearly the peak plasma density was observed (x = 0 mm, y = 5.0 mm, and z = 2.0 mm). In the velocity phase space, the following relation for the trapped electron is derived: 34…”
Section: Loss Cone Of the Magnetic Mirrormentioning
confidence: 99%